Evaluation of Fractional CO2 Laser Efficacy in Acne Scar - Saryazdi, Simin; Mohebbi, Azadeh (Journal of Lasers in Medical Sciences, 2012)
INTRODUCTION: Acne scar is formed after severe episodes of acne in teen and earlyadult years. Several treatment options have been used for depressed acne scars suchas punch grafting, punch excision carbon dioxide (CO2) laser etc. Moreover, Studiesshow that laser skin resurfacing such as CO2 fractional can effectively treat depressedacne scars. We investigated the efficacy of fractional CO2 laser in acne scar. METHODS: In this clinical trial; we used CO2 fractional laser (Unit: eCO2 LutronicKorea; FDA approved) in 15 female cases with an age range of 20-40 years old.They underwent 3 sessions of laser resurfacing at one month intervals. In the first session we used laser with a density of 150 and fluency of 70 with a 4mm diameter circular spot in static mode on depressed acne scars, and we exerted laser with density of 100 and fluency 70 with 12 mm diameter square spot in static mode on all involved skin in the other sessions. Photographs were taken before every process. The patients and another dermatologist filled the questionnaire concerning the percent of improvement. Finally, we compared photographs and evaluated the efficacy of CO2 fractional laser in acne scars. RESULTS: Objective and subjective improvement was estimated about 20-70% and 30-70%, respectively, without any erythema, permanent hyperpigmentation and other adverse effects. The important point is that, participants returned back to work after 4-7 days. CONCLUSION: The Fractional CO2 laser resurfacing can be used as a safe and efficacious method to treat depressed acne scar.